Pengaruh Penerapan E-Kinerja dan Tunjangan Kinerja terhadap Kinerja di Mediasi Motivasi Kerja: Pada Pegawai di Balai Pengkajian Teknologi Pertanian (BPTP) Papua - Karrang , Yohanis T.; Tuhumena, Ruben; Syauta, Jack (Adhigana Papua: Jurnal Ilmiah Magister Manajemen, 2023)
This study aims at the effect of implementing e-performance and performance allowances on performance in the mediation of work motivation in employees at the Agricultural Technology Assessment Center (BPTP) Papua. Research Objectives: 1. Effect of e-performance on work motivation, 2. Effect of performance allowances on employee motivation, 3. Effect of work motivation on employee performance, 4. Direct and indirect effects of e-performance through intervening work motivation on employee performance, 5. The direct and indirect effects of performance allowances through intervening work motivation on the performance of employees of the Papua Agricultural Technology Study Center. The number of samples is 41 people, the sampling technique uses saturated samples. Test the direct effect hypothesis and the Sobel test with SPSS 23. The results of the study: 1. E-performance has a positive and significant effect on employee motivation at AIAT Papua. 2 Performance Allowances have a positive and significant effect on employee motivation at BPTP Papua. 3 Work motivation has a positive and significant effect on employee performance. 4 E-Performance directly has no significant positive effect on employee performance, while indirectly e-Performance through Work Motivation has a significant effect on employee performance at AIAT Papua. 5 Performance Allowances directly have a significant positive effect on BPTP Papua employee performance, while indirectly Performance Allowances through work motivation have a significant effect on BPTP Papua employee performance.